Impacto del estrés hídrico en la anatomía de la madera y morfología de Acacia macracantha willd. y Cinchona officinalis L. bajo condiciones de invernadero - Feijoo Feijoo, Cesar Emiliano (2020)
The productivity of forest ecosystems from an ecological point of view is directly related to the production of biomass, and from a commercial point of view to the wood production. This study tries to understand how climate variations and especially water stress influences the carbon fixation or cellulose formation, as well as morphological changes in forest species. For this purpose, seedlings of Cinchona officinalis and Acacia macracantha within a greenhouse were subjected to several water stress treatments, and a vertical incision in the xylem was made with a scalpel as a reference for the beginning of the treatment. A control treatment (T0), two treatments of moderate drought with and without fertilizer (T1, T3), and two treatments of severe drought with and without fertilizer (T2 and T4) were used. After continuous weekly monitoring after six months from April to October 2019, fine microscopic cross sections of the seedlings' stems were made at the UNL Tropical Wood Anatomy Laboratory. Through the color difference of Astrablau and Safranina in the anatomical cuts it was possible to quantify the percentages of lignin and cellulose with the help of ICY image bioanalysis software using eight color separation channel filters. Additionally, changes in morphological variables (height, diameter, phytosanitary status, number of leaves and mortality) were analyzed with principal component analysis, boxplots, and correlation charts with the help of the R statistical programming platform. The results allowed us to determine that water resistance, lignin and cellulose percentages, and the reaction of morphological variables depend mainly on each species and its origin. Cinchona officinalis proved to be much more sensitive to water stress than Acacia macracantha. In C. officinalis, a decrease in carbon (cellulose) fixation due to water stress was considerably evident, but it had a more homogeneous morphological change among individuals. On the contrary, A. macracantha presented greater cellulose production, but had greater morphological changes between treatments and individuals due to hydric stress. Fertilizer did not influence the resistance to water stress, both anatomically and morphologically; on the contrary, it was possible to show that individuals containing fertilizer had higher mortality within both species. Cinchona officinalis did not support drought periods longer than four weeks, while Acacia macracantha supported droughts of up to eight weeks. Research of this type allows us to know the adaptability and resilience of forest species to strong climatic impacts. Therefore, it is necessary to complement future research related to the impact of water stress on carbon fixation (cellulose) and wood production, as well as the determination of morphological changes in forest species, in order to contribute to the generation of knowledge of native species resistant to global warming with prolonged droughts. Keywords: lignin, cellulose, morphological variables, water stress, carbon sequestration